Excellent Response to Alectinib in ALK Positive NSLC Adenocarcinoma, Case Report and Literature Review - Ismaili, Irfan; Pachoska Stojchevska, Vesna; Gjeorgjieva Janev, Olivera (Macedonian Association of Anatomists and Morphologists, 2023)
Non small cell lung carcinoma (NSCLC) is a type of lung carcinoma that slowly grows within the lung tissue. Hence, it is often diagnosed late when the disease has already progressed and passed to other body organs and/or lymph nodes. In most cases, this makes NSCL inoperable at the exact moment of diagnosing, which leads to the necessity of using chemotherapy that has the purpose of narrowing the extended masses in the lungs and/or any near/further metastases. Alectinib is a tyrosine k inase inhibitor (TKI) that is currently being used as a first line target therapy in treating the inoperable ALK rearranged NSCLC, but still the effectiveness of the treatment is not definitely known and examined. Herein, we present the case of a 51 year old male patient admitted to our hospital with hemoptysis for 2 weeks. Contrast enhanced computerized tomography (CT) of the chest showed an approximately 28x23 mm soft tissue mass infiltrating the lumen of the right bronchus and causing obstruction. On the same side at the base, a hypodense nodule of 19 mm with some surrounding pneumonic reaction and irregular contours was detected. Several significant lymph nodes were detected in the hilar and mediastinal regions. Bronchial biopsy of the mass showed pulmonary adenocarcinoma and the immunohistochemical testing results confirmed ALK rearrangements. TKI Alectinib was given at a dosage of 600mg twice per day for 13 cycles, achieving a complete response of the disease with complete regression of the mass in the right bronchus, complete regression of the right nodule and hilar and mediastinal lymph nodes were not detected following the treatment. The patient continued to receive Alectinib and did not report any specific discomfort at his 13th month follow up.
Keywords: NSCLC; Lung adenocarcinoma; ALK rearrangement; TKIs; Alectinib